Design of the Ship Officer’s Bridge for Autonomous Electric Water Shuttles - Richmond, Katie; Salih, Aya (My University, 2024)
This project is conducted to design an area that ensures the safety and comfort of the ship officer and the passengers on CStrider’s boats. The main objective is to provide a concept for the ship officer’s bridge that CStrider AB can use as a basis for future development and testing. The project utilizes an approach that includes multiple steps to achieve said objective. A planning and preparation phase was conducted to frame the project, analyze competitors and identify stakeholders. This research helps identify necessary parameters for the development of the space. Based on the findings from the previous phases, two concepts emerge from a concept generation and elimination phase that are presented to CStrider. One concept is developed with comfort as the main factor and the other with space-saving as the main factor. An additional concept for the counting system that does not include the space is also presented. After revising said concepts, they are prototyped at actual scale using low-resolution materials in CStrider’s workshop. Testing candidates are brought in to the workshop to perform some role playing scenarios where they pretend to be a ship officer as they board passengers, utilize their space, and lastly, deboard the passengers. Feedback is given from the candidates and analyzed. After the feedback from the conducted tests, a final concept emerges which is a combination between the comfortable concept and the space-saving concept to reach an optimal design. The result includes a space that contains adjustable seating, a standing mat, a dashboard with large buttons with decals and embossed labels as well as adjustable screens, a visor over the dashboard, storage for personal items and lastly, a handle. The space is contained by a front wall that has an L shape which is mainly transparent but opaque up to the height of the locker as well as a paneled emergency door that folds into the corner when not in use. A hook is placed on the outside of the L extension to provide the ship officer the ability to hang wet clothes or accessories. Lastly, an FMEA is performed to identify potential failure modes in the components that the concept consists of. The outcome from this project can be used as a foundation by CStrider to further develop their optimal ship officer space and recommendations for the future are presented. Recommendations include further steps that CStrider can take to validate the result of the project, as well as recommendations of alterations to the final design to lower the costs if desired.
Keywords: Autonomous boats; product development; user-centered design; ship bridge